Development of a functionally sustainable system of orientation of a free battle flighting unit - Zhezhera, Ivan; Ouissam, Boudiba; Firsov, Sergei (Eastern-European Journal of Enterprise Technologies, 2017)
Our approach to implementation of a functionally stable orientation system using software-hardware redundancy of measuring systems of small autonomous aerial vehicles is presented. The authors substantiated the possibility of introduction of optical systems using the algorithms of computer vision in order to provide necessary redundancy and to allow functionally stable control of small autonomous aerial vehicles. Developments in this area enjoy great demand due to the need to increase safety level of aerial vehicles in case of emergency situations. The use of camera’s visual information as an additional source of geospatial information for provision of redundancy and implementation of majority calculation was proposed. As a result of the research, algorithmic dependence of signals of orientation system was established, which made it possible to perform analysis and diagnosis with subsequent restoration of the lost parameter thanks to hardware-software redundancy of devices. Dichotomous algorithms of diagnosis and the block-diagram of reconfiguration of the classical system of orientation in the real-time mode for common types of failures were presented in the paper. Practical application of the system under real conditions with the influence of artificially created obstacles was demonstrated. The functionally stable orientation system will enhance efficiency of existing unmanned aerial vehicle and reduce the risk of losing an aerial vehicle while performing a task. In comparison with currently existing correlation – optical systems, the orientation system, described in the work, makes it possible to provide functional stability through constant monitoring all measuring bodies and timely pairing of failures. In this case, a clear advantage is operation at minimal hardware redundancy of measuring bodies